Ordo initiationis christianae adultorum przykładem recepcji katechumenatu wczesnochrześcijańskiego w teologii liturgicznej Aidana Kanvanagha (1929-2006) - Głowacki, Zbigniew Michał (Vox Patrum, 2020)
The restoration to the Church, after the Second Vatican Council, of the catechumenate based on patristic sources is a return to the traditional treatment of Christian initiation. In the light of the liturgical theology of Aidan Kavanagh, the model of Christian initiation for adults is today, as it was in the times of the Church Fathers, a basic model and one that responds to the times. This return to the original catechumenate is expressed in treating initiation as a process based on conversion, on a path of catechesis in mystery and mystagogy. The sacraments are an inseparable element here, seen as an entry into the mystery of Christ and closely connected with catechesis. The model of the current initiation of adults, being a restoration of the ecclesiology of the first centuries, is the paradigm of Christian life and an example of the reception of the patristic catechumenate.